Students’ Perspectives on the Use of PayLater Services from the Perspective of Islamic Law and Financial Technology (FinTech) - Angela Phelia; Chika Raisa Ayu Nazira; Dwina Fitria Salamah; Khalisha Anggita Apriliyani; Linda Sukmawati; Muhammad Wildan Ramadan; Edi Suresman (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The digital technology revolution has driven a massive transformation in the financial system through the emergence of financial technology (fintech), one of which is the paylater service. Currently, the convenience of paylater actually impacts consumer behavior and sparks legal implications in Islamic economics. The purpose of this study is to analyze the views of university students in Bandung on the use of paylater based on Islamic law and fintech perspectives. The research method is descriptive quantitative, with a questionnaire spread to 53 university students in Bandung. The result indicates that students have a good understanding of the paylater mechanism, including its interest rates and late fees. However, from an Islamic law perspective, the majority of respondents consider that conventional paylater services potentially contain elements of usury (riba) and uncertainty (gharar), meaning they are not fully in accordance with sharia principles. There is a dilemma between adhering to sharia principles and the reality of urgent needs and digital lifestyles. Therefore, increasing sharia financial literacy is crucial so students can make wiser financial decisions in the digital era.